A Hopf Bifurcation in a Three-Component Reaction-Diffusion System with a Chemoattraction - YoonMee Ham; Sang-Gu Lee; Quoc Phong Vu (Abstract and Applied Analysis)
We consider a three-component reaction-diffusion system with a chemoattraction. The purpose of this work is to analyze the chemotactic effects due to the gradient of the chemotactic sensitivity and the shape of the interface. Conditions for existence of stationary solutions and the Hopf bifurcation in the interfacial problem as the bifurcation parameters vary are obtained analytically.